The Peculiarities of Modern Investment Legislation of the Republic of Uzbekistan - Zaynobiddinova Farangiz (Researchparks Publishing, 2021)
Today the operating legal regulations provide an adequate state of guarantees of protection, tax benefits and preferences, incentives for foreign investors as well as government introduces new legal amendments and regulatory mechanisms to fulfill its obligations to ensure more favorable investment climate. This article discusses the implementation of an active investment policy and the issues of the modern investment legislation in the country taking into account the main tasks set by the President in the Message of 2021. Besides, the scientific work analyses the features and differences of the previous legislation of the Law of the Republic of Uzbekistan “On Investments and Investment Activities”. Moreover, based on the study, the main factors of a favorable investment environment and modern investment policy in the country are identified as an answer to the question of why investors should invest in Uzbekistan today.